Pengaruh Kondisi Ekonomi Keluarga Terhadap Perencanaan Karir Siswa - Hayanatul Fittari; Wedra Aprison; Fadhilla Yusri (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2020)
The purpose of this study is that the researcher wants to see how much influence the family economic conditions have on the career planning of students of SMAN 1 Mungka District. The population in this study were 49 students of class XII of SMAN 1 Mungka District and the samples taken were 49 students of class XII using total sampling. The results showed the regression results were positive (+), namely Ῠ = 41.537 + 1.075X. The meaning of this number is that if the family's economic condition (X) then the value of the career planning constellation (Y) is 41.537, and for each additional 1% of the family's economic condition (X), career planning will increase by 1.075. Hypothesis test results in this study found that the F count> from the F table (93.584> 4.04) thus it can be concluded that Ho is rejected and Ha accepted there is a significant influence between family economic conditions on the career planning of students of SMAN 1 Kec. Mungka, and also the determination test has been carried out, it is known that economic conditions affect the career planning of students as much as 97.8% and the remaining 2.2% is influenced by other variables outside the research variable.